The Relationship between Russian Identity and Political Polarization: The Role of Secure National Identification and National Narcissism - O.A. Gulevich; S.S. Kosimova (Социальная психология и общество)
Objective. To analyse the relationship between secure national identification and national narcissism with political polarization (intergroup differentiation between people with different political views). Background. Previous research has shown that individuals with a strong secure national identification are more supportive of their fellow citizens than those with a weaker national identity. At the same time, individuals with high levels of national narcissism exhibit more negative attitudes toward co-citizens whom they perceive as threats to the country, compared to those with lower levels of national narcissism. This suggests that secure national identification and national narcissism are associated differently with political polarization. Study design. Respondents completed questionnaires to measure secure national identification, national narcissism, and political polarization. The presence and nature of the relationships were verified through linear regression analysis. Participants. In the study, 693 Russian citizens participated (N1 = 473, N2 = 220). Respondents participated in an online survey conducted in Yandex Toloka platform (sample 1) and Anketolog (sample 2). The study involved two measurements: the first was conducted in 2023, and the second in 2024. Measurements. To measure political polarization, proprietary methodology was used. The criterion for political polarization was whether participants believed the country was moving in the right or wrong direction. Participants appraised the extent to which fellow citizens with these views exhibit certain traits; expressed emotions towards them; evaluated their willingness to interact and collaborate on common issues and considered the acceptability of restricting their rights and opportunities. To assess national identity, modified social identity and collective narcissism scales were used. Results. The current study showed that secure national identification and national narcissism are associated with more positive attitudes towards people who approve of the country’s direction, compared to those who do not. However, secure national identification is more strongly associated with positive attitudes towards fellow citizens who support status-quo compared to national narcissism. Conversely, national narcissism was more strongly related to negative attitudes towards those who oppose the status quo than secure national identification. Conclusions. Russian identity increases polarization between individuals who support vs. those who do not support the current state of affairs in the country. However, secure national identification fosters unity among Russians by encouraging a positive attitude toward citizens who support the country's current state of affairs. Conversely, national narcissism creates division by rejecting those who are critical of the status quo.